Translation on Epic Literary Theory: Andrew M. Ramsay’s «Discours de la poésie épique» (1716) translated by an Spanish Enlightened (Castilla. Estudios de Literatura, 2021)
In 1716, Andrew M. Ramsay published a speech in defence of Fénelon's epic work Les aventures de Télemaque (1699). Later, in 1756, the lawyer José Linares y Montefrío translated the speech into Spanish. Although the censorship of the Spanish edition guarantees the accuracy of the translation, a comparison of the two texts reveals that it is an adaptation of the speech by the translator. In it, Ramsay critically comments on the theoretical ideas of the epic, differentiating himself from the contemporary trend of classical aesthetics, as opposed to what Linares and Montefrío have stated, which is evidently indebted to a trend with national overtones. It analyses how literary theory is translated in lenguage and ideas to the text from which it comes and, depending on a conceptual framework designated by the aesthetic-literary trends of each nation, supports or questions some precepts.
Keywords: epic theory; translation; Enlightenment; Andrew M. Ramsay; José Linares y Montefrío